PERBEDAAN PENGARUH LATIHAN HURDLE DRILL DAN CONE DRILL TERHADAP PENINGKATAN AGILITY PADA ATLET BADMINTON - Bayu Syuhada Putra; Shofhal Jamil; Tyas Sari Ratna Ningrum (Bajang Institute, 2025)
Background: Agility plays a crucial role in the performance of badminton athletes, with the ability to change direction quickly and efficiently. A decline in agility in young athletes often arises from monotonous training programs without specific directional change stimulation. Hurdle drill and cone drill interventions are needed to improve neuromuscular coordination and leg muscle strength. However, the relative effectiveness of both on badminton athletes has been minimally researched. Objective: This study aims to determine the effect of hurdle drill and cone drill training on improving agility in badminton athletes, as well as the differences in their effects. Methods: This study used an experimental design with a two-group pretest-posttest design. The sample consisted of 26 badminton athletes aged 7-11 years at the PB Fury Sport Yogyakarta Club, selected using purposive sampling and divided into two groups (13 people each). Group I was given hurdle drill training and Group II was given cone drill training, with a frequency of 3 times a week for 3 weeks. Agility measurements were taken using the Illinois Agility Test before and after the intervention. Results: The paired sample t-test results showed p=0.000 (p<0.05) in Group I and p=0.000 (p<0.05) in Group II, indicating a significant increase in agility in both groups. However, the independent sample t-test showed p=0.918 (p>0.05), indicating no significant difference between the two exercises. Conclusion: Both exercises were effective in improving agility in badminton athletes